2021
DOI: 10.1016/j.phymed.2021.153494
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo-controlled pilot clinical trial on the efficacy of ayurvedic treatment regime on COVID-19 positive patients

Abstract: Background Specific treatment for COVID-19 is still an unmet need. Outcomes of clinical trials on repurposed drugs have not been yielding success. Therefore, it is necessary to include complementary approaches of medicine against COVID-19. Purpose This study was designed to evaluate the impact of traditional Indian Ayurvedic treatment regime on asymptomatic patients with COVID-19 infection. Study design It is a placebo controlled randomized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 31 publications
0
65
0
3
Order By: Relevance
“…The recovery response rate in the treatment group was higher than the control group. The probability of delayed healing process from infection in the treatment group was significantly decreased by 40% (Devpura et al, 2021).…”
Section: Tinospora Cordifolia and Piper Longummentioning
confidence: 92%
“…The recovery response rate in the treatment group was higher than the control group. The probability of delayed healing process from infection in the treatment group was significantly decreased by 40% (Devpura et al, 2021).…”
Section: Tinospora Cordifolia and Piper Longummentioning
confidence: 92%
“…This needs further trial on a large group to be actually established into a valid drug against SARS-CoV-2. Clinical trial of ashwagandha in combination with Swasari Ras, Giloy Ghanvati, Tulsi Ghanvati and Anu Taila was done on mildly affected and asymptomatic patients (Clinical Trial Registry-India -6) and tumor necrosis factor alpha (TNF-a) [9]. All these observations provide a constructive lead towards their usage as drugs or dietary supplement in a dose specific manner for managing the progression of this viral disease.…”
Section: Resultsmentioning
confidence: 99%
“…A large effort has been put in by the Ministry of AYUSH, GOI, to validate these drugs (21). A randomized placebo controlled short term study attempted to show a reduction in viral load using a well-designed Ayurvedic regimen (oral drugs and nasal application) in asymptomatic and mild cases of COVID-19; clinical improvement was not properly defined (47). A small sample size uncontrolled observational study showed good resolution of symptoms by AYUSH 64 in patients suffering from influenza like illness (48).…”
Section: Other Studiesmentioning
confidence: 99%